2020
DOI: 10.1002/suco.201900339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on flexural cracking behavior of ultrahigh performance concrete beams

Abstract: The flexural cracking behavior of ultrahigh performance concrete (UHPC) beams was experimentally studied in this paper. Eight UHPC beams were tested and analyzed regarding their crack pattern, crack spacing and loadcrack width curves. The test variables included reinforcement ratio, reinforcement diameter and UHPC cover thickness. The results indicated that crack width of UHPC increased linearly with the increase of applied load until the yielding of steel rebars. When the applied load was beyond the yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 20 publications
0
9
1
5
Order By: Relevance
“…Additionally, this figure demonstrated that increasing ρ notably decreases the crack opening width of the UHPC beams at the same service loading. It is worth noting that this finding is inconsistent with that reported by Qiu et al [52]. Another significant observation is that increasing reinforcement ratio contributed to stabilizing the crack propagation, as the slope of the UHPC beam's load-crack curve increases as its bar reinforcement increases.…”
Section: Ductility Analysiscontrasting
confidence: 72%
“…Additionally, this figure demonstrated that increasing ρ notably decreases the crack opening width of the UHPC beams at the same service loading. It is worth noting that this finding is inconsistent with that reported by Qiu et al [52]. Another significant observation is that increasing reinforcement ratio contributed to stabilizing the crack propagation, as the slope of the UHPC beam's load-crack curve increases as its bar reinforcement increases.…”
Section: Ductility Analysiscontrasting
confidence: 72%
“…17 However, the effect of reinforcement diameter and UHPC cover thicknesses on the flexural performance of reinforced UHPC beams is not well understood. 18 In addition, many scholars have proposed the prediction model of flexural capacity for rebar-reinforced UHPC beams or steel fibers reinforced beams. [19][20][21][22] However, they mainly focus on the prediction of the maximum load considering the contribution of UHPC's tensile strength and reinforcement's yielding strength.…”
Section: Introductionmentioning
confidence: 99%
“…As above‐mentioned, the flexural and ductile behaviors of reinforced UHPC beams have been well investigated by many researchers, and their investigations mainly focus on the effects of reinforcement ratio, 9–15 fiber properties, 8,10,12,15,16 and type of reinforced bars 17 . However, the effect of reinforcement diameter and UHPC cover thicknesses on the flexural performance of reinforced UHPC beams is not well understood 18 …”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of using UHPC to enhance the torsion resistance of reinforced concrete beams was justified by experimental work 16 . Qiu 17 conducted an experimental study on the flexural cracking behavior of UHPC beams. Eight UHPC beams were tested and analyzed regarding their crack pattern, crack spacing and load‐crack width curves.…”
Section: Introductionmentioning
confidence: 99%